EXPLORING SEVEN DECADES OF TAX EVASION RESEARCH: A GLOBAL BIBLIOMETRIC MAPPING - Razali, Rosnazida; Ismail, Ida Suriya; Abd Hamid, Nadiah (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME’S (AIJBES), 2025)
This study provides a comprehensive bibliometric mapping of tax evasion research spanning seven decades, addressing the need to understand the evolving intellectual structure and global scholarly contributions within this critical field. Despite extensive research, the field lacks a consolidated overview of key authors, influential countries, and collaborative networks, which limits the strategic direction for future studies and policy development. Employing bibliometric techniques, this study analyzed 916 peer-reviewed articles retrieved from the Scopus database, with data cleaning and standardization performed using OpenRefine, and visualized through VOSviewer software to map co-authorship, keyword co-occurrence, and citation patterns. The results reveal that seminal authors such as Robert W Mac Ghee, Friedrich Schneider, and James Alm have been pivotal in shaping the discourse, while the United States, Italy, and Germany dominate in terms of publication volume and citation impact. Emerging economies, such as Malaysia, China, and South Africa, demonstrate a growing research presence but exhibit limited intra-regional collaboration, as evidenced by co-authorship network analyses. Keyword trends indicate a gradual shift from traditional tax evasion themes to more nuanced areas, including behavioral determinants and policy responses. The findings highlight a significant Western-centric research dominance yet emphasize the increasing importance of developing countries in contributing diverse perspectives. This bibliometric mapping provides valuable insights for academics and policymakers aiming to foster more inclusive and contextually relevant tax evasion research, ultimately supporting more effective tax compliance strategies worldwide.